Teacher man : a memoir - McCourt, Frank (New York : Scribner, 2005)
Celebrated American author Frank McCourt recounts his thirty-year teaching career, and describes some of his unconventional teaching methods that have left an impact of his students.
Kirkus Starred
Library Journal Starred
Pub Weekly
Adult.
Adult
Keywords: McCourt, Frank; McCourt, Frank; High school teachers -- New York (State) -- New York -- Biography; Irish Americans -- Biography; Irish Americans -- Biography; Teachers -- New York (N.Y.) -- Biography